A Prospective Nested Case-Control Study of Risk Factors for Postoperative Delirium in Elderly Patients with Colorectal Cancer - Cui X; Cao N; Tian S; Liu Y; Xiang J (Clinical Interventions in Aging, 2025)
Xinlong Cui,1 Naihan Cao,2 Shouyuan Tian,1 Yi Liu,1 Jie Xiang3 1Department of Anaesthesiology, Shanxi Province Cancer Hospital (Shanxi Hospital Affiliated to Cancer Hospital, Chinese Academy of Medical Sciences, Cancer Hospital Affiliated to Shanxi Medical University), Taiyuan, Shanxi, 030013, People’s Republic of China; 2College of Anesthesia, Shanxi Medical Universiy, Taiyuan, 030001, People’s Republic of China; 3College of Computer Science and Technology (College of Big Data), Taiyuan University of Technology, Taiyuan, 030002, People’s Republic of ChinaCorrespondence: Yi Liu, Email 170767909@qq.comPurpose: The objective of this study is to investigate the risk factors associated with postoperative delirium (POD) in elderly patients diagnosed with colorectal cancer (CRC).Patients and Methods: This prospective nested case-control study included elderly patients who underwent CRC surgery at Shanxi Provincial Cancer Hospital between May 2022 and September 2023. A propensity score matching (PSM) method was employed to match patients by age and sex. Univariate and multivariate logistic regression analyses were conducted to identify independent risk factors for POD among elderly patients with CRC.Results: A total of 443 patients were enrolled, among them, 70 (15.8% of all patients, age: 69.5[64, 73], 55 [78.6%] males) developed POD and 373 did not develop POD (84.2% of all patients, age: 67[62, 71], 234 [62.7%] males). Following PSM at a 1:3 ratio, 70 POD patients and 210 age- and sex-matched non-POD patients were selected for further analysis. The POD group exhibited a significantly higher sleep quality score (9 [6, 15] vs 7.5 [3, 12], P = 0.004), greater intraoperative infusion volume (2041.43± 724.37 vs 1814.05± 653.83, P = 0.015), and elevated peak pain levels post-surgery (1 [0, 2] vs 1 [0, 1], P = 0.001). Univariate and multivariate logistic regression analyses identified higher education level (OR: 0.503 [0.259– 0.977]) as an independent factor associated with lower POD risk, whereas higher sleep quality scores (OR: 1.103 [1.040– 1.171]) and increased peak pain levels post-surgery (OR: 1.727 [1.295– 2.304]) were identified as independent risk factors.Conclusion: Elevated peak postoperative pain levels, lower education levels, and sleep dysfunction or disturbance are independent risk factors for developing POD.Keywords: colorectal cancer, postoperative delirium, risk factors, elderly, sleep quality, pain level, prospective nested case-control study